Semiconductor device, method for manufacturing semiconductor device, solar cell, and method for manufacturing solar cell

By entering the silicon layer and ensuring their penetration by using the MACE method, the problem of the impact of the bonding interface oxidation region in intelligent stacking technology is solved, the bonding strength and performance of semiconductor devices and solar cells is improved, and the reliability of solar cells is improved. and photoelectric conversion efficiency.

CN119318226APending Publication Date: 2025-01-14NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380044229.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-14
Filing Date
2023-05-01
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the existing intelligent stacking technology, the arrangement and oxidation region of conductive nanoparticles at the bonding interface lead to limited reliability and battery performance of semiconductor devices and solar cells.

Method used

By entering the silicon layer, it penetrates into the silicon layer of the semiconductor element to form a stable bonding structure. The conductive nanoparticles are selectively eroded by metal-assisted chemical etching method (MACE method) to ensure that they enter the silicon In the layer, the impact of the oxidation region is reduced.

Benefits of technology

It has achieved the improvement of bonding strength and battery performance of semiconductor devices and solar cells, reduced junction resistance and optical loss, and improved the reliability and photoelectric conversion efficiency of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318226A_ABST
    Figure CN119318226A_ABST
Patent Text Reader

Abstract

Provided are a semiconductor device and a solar cell having a bonding structure that improves the reliability of the semiconductor device and the solar cell, and methods for manufacturing the semiconductor device and the solar cell. A semiconductor device or a solar cell is provided with: a first semiconductor element SB1 including a silicon layer and having a first junction surface; a second semiconductor element SB2 having a second bonding surface facing the first bonding surface; and a plurality of conductive nanoparticles 23 located between the first bonding surface and the second bonding surface and electrically connecting the first semiconductor element SB1 and the second semiconductor element SB2, the plurality of conductive nanoparticles 23 entering the silicon layer. In addition, a method for manufacturing a semiconductor device or a solar cell includes preparing a first semiconductor element SB1 and a second semiconductor element SB2, disposing a plurality of conductive nanoparticles 23 on a first junction surface of the first semiconductor element SB1, causing the plurality of conductive nanoparticles 23 to enter a silicon layer, and forming a second junction surface of the second semiconductor element SB2. Then, the second bonding surface faces the first bonding surface with a plurality of conductive nanoparticles (23) therebetween and is pressed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a semiconductor device and a method for manufacturing the same, and a solar cell and a method for manufacturing the same, and, for example, to a technology that is effectively applied to a bonding layer used for stacking a plurality of solar cell cells. Background Art

[0002] As a semiconductor device, there is known a semiconductor device in which a first semiconductor element and a second semiconductor element composed of different semiconductor materials are electrically connected and stacked at the same time. For example, as such a semiconductor device, there is a multi-junction solar cell. A multi-junction solar cell is a solar cell that can achieve high performance by stacking multiple units. For example, it is expected that a multi-junction solar cell that uses a high-efficiency GaAs-based solar cell as a top unit (light-receiving side) and a low-cost Si-based solar cell as a bottom unit (non-light-receiving side) can be realized as a high-efficiency and low-cost solar cell. In addition, as a manufacturing method, there is a method of stacking the top unit and the bottom unit using a crystal growth technology, and a method of mechanically stacking using a bonding technology (mechanical stacking method).

[0003] For example, as a mechanical stacking method, there is a bonding technology (hereinafter referred to as smart stacking technology) in which conductive nanoparticles such as Pd are arranged on the bonding interface and the top unit and the bottom unit are bonded via them (Patent Document 1, Non-Patent Document 1). In addition, with respect to the smart stacking technology, the surface treatment of the bonding surface has been further studied (Non-Patent Documents 2, 3).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 5875124

[0007] Non-patent literature

[0008] Non-patent document 1: H. Mizuno, et al., Japanese Journal of Applied Physics 55, 025001 (2016)

[0009] Non-patent document 2: K.Makita, et al., 35th European Photovoltaic Solar Energy Conference and Exhibition, (2018), p20-22.

[0010] Non-patent document 3: K.Makita, et al., Progress in Photovoltaics, Research and Applications, 28, (2020), p16-24. Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] In the smart stacking technology described in the above-mentioned documents, the top unit and the bottom unit are electrically connected by conductive nanoparticles. However, since the battery performance and the quality of the semiconductor device are affected by the bonding structure, the bonding structure is important and is also related to the reliability of the semiconductor device and the solar cell.

[0013] An object of the present invention is to provide a semiconductor device and a solar cell having a junction structure that improves the reliability of the semiconductor device and the solar cell, and a method for manufacturing the same.

[0014] Technical solutions for solving technical problems

[0015] In order to solve the above technical problems, the inventors conducted in-depth research and found that by allowing the conductive nanoparticles that electrically connect the first semiconductor element and the second semiconductor element to enter the silicon layer of the first semiconductor element, the electrical connection between the first semiconductor element and the second semiconductor element is improved and a stable bonding structure is formed. This is also related to the improvement of battery performance and the quality of semiconductor devices. Specifically, the following structure is adopted.

[0016] (1) A semiconductor device in one embodiment comprises: a first semiconductor element including a silicon layer and having a first bonding surface; a second semiconductor element having a second bonding surface opposite to the first bonding surface; and a plurality of conductive nanoparticles located between the first bonding surface and the second bonding surface, electrically connecting the first semiconductor element to the second semiconductor element, wherein the plurality of conductive nanoparticles enter the silicon layer.

[0017] (2) In addition, a solar cell in one embodiment comprises the semiconductor device described in (1), wherein the silicon layer of the first semiconductor element includes a semiconductor material of crystalline silicon or amorphous silicon, and the second semiconductor element includes one or more semiconductor materials selected from the group consisting of GaAs, AlGaAs, InGaP, InGaAsP, AlGaInP, InGaAs, chalcogenide system, perovskite system, and organic system.

[0018] (3) A method for manufacturing a semiconductor device in one embodiment comprises: (a) a step of preparing a first semiconductor element including a silicon layer and having a first bonding surface; (b) a step of preparing a second semiconductor element having a second bonding surface; (c) a step of disposing a plurality of conductive nanoparticles on the first bonding surface; (d) a step of allowing the plurality of conductive nanoparticles to enter the silicon layer after the step (c); and (e) a step of allowing the second bonding surface to face the first bonding surface through the plurality of conductive nanoparticles and pressing the second bonding surface after the step (d).

[0019] (4) In addition, a method for manufacturing a solar cell in one embodiment includes the method for manufacturing a semiconductor device described in (3), in which a semiconductor material of crystalline silicon or amorphous silicon is used as the silicon layer of the first semiconductor element, and one or more semiconductor materials selected from GaAs, AlGaAs, InGaP, InGaAsP, AlGaInP, InGaAs, chalcogenide system, perovskite system, and organic system are used as the second semiconductor element.

[0020] Effects of the Invention

[0021] According to one embodiment, a semiconductor device and a solar cell having a junction structure that improves the reliability of the semiconductor device and the solar cell, and a method for manufacturing the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a diagram showing the structure of a semiconductor device (multi-junction solar cell) according to this embodiment.

[0023] Figure 2 is a schematic diagram illustrating a method for manufacturing a multi-junction solar cell.

[0024] Figure 3 It is a diagram for explaining the principle of the metal assisted chemical etching (MACE) method.

[0025] Figure 4 This is a diagram showing the structure of a multi-junction solar cell according to another embodiment 1 (example).

[0026] Figure 5 This is a diagram showing the structure of a multi-junction solar cell according to another embodiment 2.

[0027] Figure 6 This is a diagram showing the structure of a multi-junction solar cell according to another third embodiment.

[0028] Figure 7 This is a diagram showing the structure of another example of a multi-junction solar cell.

[0029] Figure 8This is a diagram showing the structure of another example of a multi-junction solar cell.

[0030] Fig. 9 is a graph showing the relationship between voltage and current density of a multi-junction solar cell.

[0031] Fig.10 is an atomic force microscope (AFM) photograph of a multi-junction solar cell on a Si surface after MACE treatment (Example).

[0032] Fig.11 These are atomic force microscope images of the Si surface of a multi-junction solar cell without MACE treatment (A) and with BHF treatment (B) (comparative example).

[0033] Fig.12 These are photographs of various multi-junction solar cells (samples AC).

[0034] Fig.13 These are photographs of each multi-junction solar cell (samples AC) after nitrogen blowing.

[0035] Fig.14 It is a figure which shows the TEM image of sample A and the analysis result by energy dispersive X-ray spectroscopy (TEM-EDX) (Example).

[0036] Fig.15 It is a figure which shows the TEM image of sample B and the analysis result by energy dispersive X-ray spectroscopy (TEM-EDX) (comparative example). DETAILED DESCRIPTION

[0037] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the same reference numerals in the drawings represent the same or corresponding parts. It should be noted that in this specification, when a numerical range is shown, the upper limit and the lower limit are included.

[0038] (Implementation Method 1)

[0039] The technical idea of ​​the present embodiment can be widely applied to a semiconductor device in which a first semiconductor element and a second semiconductor element made of different semiconductor materials are electrically connected and stacked. The technical idea will be described below using a solar cell as an example. Figure 1 FIG. 2 shows a configuration diagram of a semiconductor device (multi-junction solar cell) according to this embodiment. Figure 1In the figure, the multi-junction solar cell 1 has a solar cell element SB1 of a bottom unit and a solar cell element SB2 of a top unit. Here, the solar cell element SB1 is composed of a silicon unit. On the other hand, the solar cell element SB2 is composed of a GaAs unit. The multi-junction solar cell is a solar cell that combines units of different properties. It is composed of a transparent "top unit" on the upper layer where sunlight directly enters and a "bottom unit" on the lower layer. By combining different materials, it is possible to utilize light of a wide range of wavelengths, which has the advantage of improving conversion efficiency. It should be noted that in the specification, solar cell elements are sometimes referred to as units.

[0040] The solar cell element SB1 of the bottom unit has a p-type silicon substrate 13 on which a p-type electrode 11 is formed, and an n-type silicon layer 15 formed on the p-type substrate 13. In addition, the solar cell element SB2 of the top unit has a p-type GaAs layer 17 that functions as a light absorbing layer, an n-type GaAs layer 19 formed on the p-type GaAs layer 17, and an n-type electrode 21 formed on the n-type GaAs layer 19. Figure 1 As shown, the solar cell element SB1 and the solar cell element SB2 are joined by a plurality of conductive nanoparticles 23. Thus, the solar cell element SB1 and the solar cell element SB2 are mechanically joined and electrically connected. For example, as the conductive nanoparticles 23, nanoparticles composed of palladium (Pd) can be used.

[0041] In such a multi-junction solar cell 1, when sunlight containing visible light and infrared light is irradiated from above the solar cell element SB2, the sunlight irradiates the n-type GaAs layer 19 which is a component of the solar cell element SB2, and is incident on the n-type GaAs layer 19 and the p-type GaAs layer 17 located below the n-type GaAs layer 19. At this time, since the n-type GaAs layer 19 and the p-type GaAs layer 17 have a band gap of 1.42eV, light with light energy of more than 1.42eV in the sunlight is absorbed. Specifically, the electrons existing in the valence band of the GaAs layer (n-type GaAs layer 19 and p-type GaAs layer 17) receive the light energy supplied from the sunlight and are excited to the conduction band. As a result, the electrons accumulate in the conduction band, and holes are generated in the valence band. In this way, by irradiating the solar cell element SB2 with sunlight, the light with light energy of more than 1.42eV contained in the sunlight is used to excite the electrons to the conduction band of the GaAs layer, and holes are generated in the valence band of the GaAs layer. In addition, the conduction band of the n-type GaAs layer 19 constituting one side of the pn junction is located at a lower energy position from the electronic point of view than the conduction band of the p-type GaAs layer 17 constituting the other side of the pn junction. As a result, the electrons excited to the conduction band move to the n-type GaAs layer 19, and the electrons are accumulated in the n-type GaAs layer 19. On the other hand, the holes existing in the valence band move to the p-type GaAs layer 17, and the holes are accumulated in the p-type GaAs layer 17. As a result, an electromotive force (V1) is generated between the p-type GaAs layer 17 and the n-type GaAs layer 19.

[0042] On the other hand, sunlight with a light energy of less than 1.42 eV is not absorbed by the GaAs layer but passes through the GaAs layer. Figure 1 In the embodiment, light having a light energy of less than 1.42 eV in the sunlight is incident on the solar cell element SB1 arranged in the lower layer of the solar cell element SB2. At this time, since the n-type silicon layer 15 and the p-type silicon substrate 13 have a band gap of 1.12 eV, the light having a light energy of less than 1.42 eV and above 1.12 eV in the sunlight is absorbed. Specifically, the electrons existing in the valence band of the silicon layer (n-type silicon layer 15 and p-type silicon substrate 13) receive the light energy supplied from the sunlight and are excited to the conduction band. As a result, the electrons are accumulated in the conduction band, and holes are generated in the valence band. In this way, by irradiating the solar cell element SB1 with sunlight, the electrons are excited to the conduction band of the silicon layer by light having a light energy of less than 1.42 eV and above 1.12 eV, and holes are generated in the valence band of the silicon layer. As a result, holes are accumulated in the p-type silicon substrate 13, and on the other hand, electrons existing in the conduction band are accumulated in the n-type silicon layer 15. As a result, an electromotive force ( V2 ) is generated between the p-type silicon substrate 13 and the n-type silicon layer 15 .

[0043] Here, the solar cell element SB1 and the solar cell element SB2 are connected in series using a plurality of conductive nanoparticles 23. That is, the solar cell element SB1 and the solar cell element SB2 are connected in series. As a result, an electromotive force (V1) and an electromotive force (V2) added together are generated in the multi-junction solar cell 1 composed of the solar cell element SB1 and the solar cell element SB2 connected in series. In addition, for example, when a load is connected between the n-type electrode 21 and the p-type electrode 11, electrons flow from the n-type electrode 21 to the p-type electrode 11 through the load. In other words, current flows from the p-type electrode 11 to the n-type electrode 21 through the load. In this way, by operating the multi-junction solar cell 1, it is possible to drive the load.

[0044] In addition, according to the multi-junction solar cell 1, it is possible to absorb both light with high light energy and light with low light energy contained in sunlight and convert them into electrical energy, thereby improving the photoelectric conversion efficiency. That is, according to the multi-junction solar cell 1, it is also possible to utilize light with low light energy that cannot be utilized in a single solar cell, and therefore it is excellent in that it is possible to improve the utilization efficiency of sunlight.

[0045] Next, the features of the multi-junction solar cell 1 according to the present embodiment will be described.

[0046] The multi-junction solar cell 1 is characterized in that it has a bonding structure in which the conductive nanoparticles 23 that bond the solar cell element SB1 and the solar cell element SB2 enter the silicon layer, in this example, the n-type silicon layer 15. This can play the role of both conductivity and mechanical bonding strength in the bonding between the solar cell element SB1 and the solar cell element SB2. The structure of the multi-junction solar cell is described in detail below.

[0047] (Solar cell element SB1)

[0048] The solar cell element SB1 has a p-type silicon substrate 13 formed with a p-type electrode 11 and an n-type silicon layer 15 formed on the p-type silicon substrate 13, which is also called a silicon unit. The p-type electrode 11 is composed of, for example, a silver film or an aluminum film. As the bottom unit, it can be cheap silicon (silicon unit) that absorbs long wavelength regions. For example, there are single crystal silicon, polycrystalline silicon, microcrystalline silicon, amorphous silicon, etc. In addition, in the solar cell element SB1, for example, the band gap is 1.12eV, and light with light energy of more than 1.12eV in sunlight is absorbed.

[0049] The solar cell element SB1 is manufactured by the following method. First, a p-type silicon substrate 13 is prepared. Then, after the surface of the p-type silicon substrate 13 is cleaned, an n-type silicon layer 15 is formed on a single side of the p-type silicon substrate 13, for example, by a thermal diffusion method or an ion implantation method. At this time, an oxidized region 25 (SiO2) of about 1 nm to 20 nm is formed on the entire or partial surface of the n-type silicon layer 15 by a high temperature treatment during thermal diffusion or by an annealing heat treatment used to activate the implanted dopant material in the ion implantation method. Finally, a p-type electrode 11 is formed, for example, by a sputtering method, as shown in FIG. Figure 1 The layer structure shown.

[0050] (Solar cell element SB2)

[0051] The solar cell element SB2 has a p-type GaAs layer 17, an n-type GaAs layer 19 formed on the p-type GaAs layer 17, and an n-type electrode 21 formed on the n-type GaAs layer 19. The n-type electrode 21 is composed of, for example, an alloy film such as AuGeNi / Au, TiAu / Au, etc. As the top unit, in addition to a high-efficiency GaAs unit that absorbs short wavelength regions, it can also be a CIGS (Cu, In, Ga, Se) layer (CIGS system unit), an InGaP layer (InGaP system unit), etc. In the solar cell element SB2, for example, if it is a GaAs unit, the band gap is 1.42eV, and light with light energy of more than 1.42eV in sunlight is absorbed.

[0052] The solar cell element SB2 is manufactured by the following method. First, a stacked structure of the solar cell element SB2, such as a p-type GaAs layer 17 and an n-type GaAs layer 19, is formed on a GaAs substrate (not shown) whose surface has been cleaned using a conventional process. The stacked structure can be formed using a crystal growth method such as an organic metal crystal growth method (MOCVD: Metal Oraganic Chemical Vapour Deposition) and a molecular beam crystal growth method (MBE: Molecular Beam Epitaxy). Then, an n-type electrode 21 is formed on the n-type GaAs layer 19 by electron beam evaporation. It should be noted that the n-type electrode 21 may be formed by other methods, for example, DC magnetron sputtering, resistance heating evaporation, screen printing, electrodeposition, etc. may be used. The n-type electrode 21 is processed into a grid shape to ensure an area through which light can pass. Then, the solar cell element SB2 is separated from the GaAs substrate using an ELO (Epitaxial lift off) method. Thus, a stacked structure of the solar cell element SB2 can be formed. In this way, an interface serving as a bonding surface is formed in the solar cell element SB2. However, since it is a surface separated from the GaAs substrate by the ELO method, flatness suitable for bonding via the conductive nanoparticles 23 is ensured.

[0053] It should be noted that the solar cell element SB1 and the solar cell element SB2 are not limited to being manufactured by the above method, and can be manufactured by a known method. In addition, it does not matter which of the solar cell element SB1 and the solar cell element SB2 is manufactured first.

[0054] (Conductive Nanoparticles 23)

[0055] The conductive nanoparticles 23 electrically connect the solar cell element SB1 and the solar cell element SB2. The conductive nanoparticles 23 enter the inside of the n-type silicon layer 15 on the side of the solar cell element SB1 and are stably maintained. As the conductive nanoparticles 23, for example, in addition to palladium, any of metal nanoparticles of gold, silver, platinum, nickel, aluminum, indium, zinc, copper, etc., indium oxide, and zinc oxide can also be used. Considering good conductivity and suppressing the absorption and scattering of light by nanoparticles, the size of the conductive nanoparticles 23 is preferably 10-500nm in diameter, and more preferably 10-100nm in diameter. In addition, the spacing of the conductive nanoparticles 23 can be set to more than 2 times and less than 10 times the average diameter of the conductive nanoparticles 23. Thus, the conductivity brought by a plurality of conductive nanoparticles 23 can be ensured, and the light transmittance at the joint portion can also be fully ensured.

[0056] The shape of the conductive nanoparticles 23 can be any shape as long as the conductivity is ensured, for example, it is not limited to a spherical shape, and can also be a columnar shape such as a quadrangular prism or a cylindrical shape, a thin wire shape, a fiber shape, an amorphous shape, etc. The shape of the conductive nanoparticles 23 can be controlled by, for example, adjusting the composition of the block copolymer described later.

[0057] In addition, in the multi-junction solar cell 1 of the present embodiment, the conductive nanoparticles 23 enter the n-type silicon layer 15 on the side of the solar cell element SB1, thereby improving the electrical connection between the solar cell element SB1 and the solar cell element SB2, and being able to form a stable bonding structure with excellent bonding strength. Therefore, according to the present embodiment, a solar cell having both bonding strength and good cell characteristics can be provided.

[0058] (Method of Joining Solar Cell Element SB1 and Solar Cell Element SB2)

[0059] based on Figure 2 and Figure 3 , the method for joining the solar cell element SB1 and the solar cell element SB2 is described. First, according to the conventional smart stacking technology, a block copolymer is used to make a small arrangement pattern of the conductive nanoparticles 23, and then the conductive nanoparticles 23 are precipitated by treating with a chloride solution, and then treated with argon plasma, so as to Figure 2 As shown in (B), conductive nanoparticles 23 are arranged. An example is shown below.

[0060] A thin film (not shown) composed of a block copolymer is formed on the surface of the solar cell element SB1 (the surface of the n-type silicon layer 15) as the bonding object. Specifically, a block copolymer is applied to the surface of the n-type silicon layer 15 using a spin coating method or a dip coating method. The block copolymer is composed of polystyrene as a hydrophobic part and poly-2-vinylpyridine as a hydrophilic part that is soluble in organic solvents such as toluene and o-xylene. As a result, due to the phase separation of the block copolymer, the poly-2-vinylpyridine block is patterned on the surface of the n-type silicon layer 15. That is, a hydrophilic domain is formed on the surface of the n-type silicon layer 15. Next, the solar cell element SB1 is immersed in an aqueous solution in which a metal ion salt represented by Na2PdCl4 is dissolved. As a result, the metal ion (Pd 2+ ) is incorporated into the pattern composed of poly-2-vinylpyridine blocks. In other words, the metal ion (Pd 2+) is selectively precipitated in the hydrophilic region. Then, after sufficient water washing, the solar cell element SB1 is subjected to a block copolymer removal treatment and a metal ion reduction treatment, for example, using argon plasma. As a result, a regular arrangement of the conductive nanoparticles 23 can be formed while maintaining the pattern ( Figure 2 (B)). It should be noted that the shape of the conductive nanoparticles 23 can be controlled by changing the degree of polymerization of the block copolymer. For example, when the degree of polymerization is set to polystyrene: poly-2-vinylpyridine = 133000: 132000, the diameter of the conductive nanoparticles is 50nm, but when poly-2-vinylpyridine is reduced to polystyrene: poly-2-vinylpyridine = 135000: 53000, the diameter of the conductive nanoparticles can be controlled to a smaller size of 25nm.

[0061] Next, when the entire solar cell element SB1 is immersed in an etching solution (e.g., a hydrogen peroxide (H2O2) / hydrogen fluoride (HF) solution), only the portion contacted by the conductive nanoparticles 23 is selectively corroded (also referred to as etching), as shown in FIG. Figure 2 As shown in (C), the conductive nanoparticles 23 sink and penetrate the oxidized area 25 and enter the n-type silicon layer 15. It should be noted that the method is not limited to immersion, and the etching solution can also be dripped or applied to the surface of the solar cell element SB1. This method is called metal assisted chemical etching (MACE) method, and the principle is as follows Figure 3 It should be pointed out that Figure 3 This is a schematic diagram for explaining the principle only. As shown in formulas (1) and (2), electrons generated by the oxidation reaction of silicon (Si) and holes generated by the decomposition of hydrogen peroxide react with the conductive nanoparticles 23 as a conductive metal interposed therebetween, promoting the oxidation reaction and forming an etching region 27. Then, as shown in formula (3), silicon dioxide reacts with hydrogen fluoride to become SiF6 discharged as etching residue.

[0062] H2O2+2H + →2H2O+2h + (1)

[0063] Si+2H2O→SiO2+4H + +4e - (2)

[0064] SiO2+2HF2 - +2HF→SiF6 2- +2H2O(3)

[0065] Then, after the other solar cell element SB2 to be joined is stacked on the solar cell element SB1 on which the conductive nanoparticles 23 are arranged, an appropriate pressurization treatment (for example, 5 N / cm 2 ), thereby bonding the solar cell element SB1 and the solar cell element SB2 ( Figure 2 In this way, the solar cell element SB1 and the solar cell element SB2 are bonded together by the conductive nanoparticles 23 .

[0066] When using conventional smart stacking technology to produce a multi-junction solar cell composed of silicon units and GaAs units, as shown in non-patent literature 2-3, due to the presence of oxidation areas on the surface of the silicon unit, the junction resistance between units in particular becomes large, which affects the characteristics of the solar cell and becomes a problem.

[0067] However, according to the present embodiment, the conductive nanoparticles 23 penetrate the oxidized region 25 and enter the low-resistance n-type silicon layer 15 of the lower side, thereby being not affected by the oxidized region 25, and the junction resistance between the cells can be improved. In particular, according to the MACE method, only the region contacted by the conductive nanoparticles 23 is selectively eroded, and the conductive nanoparticles 23 can be easily made to enter the n-type silicon layer 15. Thus, the conductive nanoparticles 23 form a stable and excellent bonding strength bonding structure through the so-called anchoring effect. Therefore, the reliability of semiconductor devices and solar cells can be improved.

[0068] In addition, in the MACE method (also referred to as MACE treatment), the sinking height of the conductive nanoparticles 23 can be adjusted by controlling the treatment time (immersion time) of the etching solution, the amount of liquid, the composition of the etching solution (for example, the molar ratio of H2O2 to HF), and the concentration of the etching solution. For example, by extending the treatment time or increasing the concentration of the H2O2 / HF solution, the range of the etching area 27 becomes larger (deeper). The oxidation area 25 is only partially etched by the H2O2 / HF solution, but in the area directly below the conductive nanoparticles such as Pd, it is selectively etched at a high speed by the effect of MACE. Then, the conductive nanoparticles 23 completely penetrate the oxidation area 25. At this time, it is desired to be located at a depth of more than 5nm in the n-type silicon layer 15.

[0069] In the smart stacking technology, the height of the conductive nanoparticles is defined as the air or adhesive at the bonding interface. Here, the air, adhesive, etc. have a low refractive index, so optical loss occurs at the bonding interface due to light reflection. However, by allowing the conductive nanoparticles 23 to penetrate deep into the silicon unit, the effective thickness of the air and adhesive can be reduced to reduce the optical loss. For example, if the interval H between the solar cell element SB1 and the solar cell element SB2 is ( Figure 1, also called the bonding gap. ) is less than 20nm, preferably less than 10nm, then the light reflection loss can be reduced to less than 10%. The interval H is equivalent to the exposure height of the conductive nanoparticles 23. By controlling the exposure height, the optical loss can be reduced. In addition, by changing the shape, size, and density of the conductive nanoparticles 23, the interval H can also be effectively controlled. In addition, the deeper the conductive nanoparticles 23 sink, the more stably the conductive nanoparticles 23 are maintained in the silicon layer. Therefore, it is more appropriate to control it to more than half of the overall height of the sunken conductive nanoparticles 23. In addition, it is better for the interval H to be infinitely close to 0 (zero), and it can also be set to 0 (zero).

[0070] (Implementation Method 2)

[0071] Figure 4 A diagram showing the structure of a semiconductor device (multi-junction solar cell) according to another embodiment. Figure 1 The multi-junction solar cell 1 shown is a solar cell composed of a double junction of a silicon unit and a GaAs unit, but the above-mentioned junction structure can also be applied to a solar cell with three or more junctions. Figure 4 The multi-junction solar cell 3 has a solar cell element SB3 of a bottom unit, a solar cell element SB4 of a middle unit, and a solar cell element SB5 of a top unit, wherein the solar cell element SB3 is composed of a silicon unit, the solar cell element SB4 is composed of a GaAs unit, and the solar cell element SB5 is composed of an InGaP unit. Specifically, the solar cell element SB4 and the solar cell element SB5 are double-junction elements of InGaP and GaAs, and the solar cell element SB3 is called a TOPCon (Tunnel Oxide Passivated Contact) silicon unit, which is a silicon unit characterized by high efficiency with reduced current loss, in which a silicon layer (amorphous or polycrystalline silicon) is formed as a contact layer with a thin film oxide layer interposed therebetween.

[0072] The solar cell element SB3 includes, for example, a p-type silicon layer (amorphous or polycrystalline silicon) 30 on which a p-type electrode 31 composed of an aluminum film or a silver film is formed, a SiOx tunnel layer 32 formed on the p-type silicon layer 30, a p-type silicon substrate 33 as a light absorbing layer, a SiOx tunnel layer 32 formed on the p-type silicon substrate 33, and an n-type silicon layer (amorphous or polycrystalline silicon) 35. Figure 1 ) Similarly, an oxidized region 25 of about 10 nm is generated on the entire surface or partially on the surface of the n-type silicon layer 35. In this way, the solar cell element SB3 is formed.

[0073] The solar cell element SB3 is manufactured by the following method. That is, it is obtained by forming a thin film tunnel layer (SiOx tunnel layer 32) composed of a SiOx oxide film on both sides of a p-type silicon substrate 33 whose surface has been cleaned, then forming a conductive polycrystalline or amorphous silicon layer (p-type silicon layer 30, n-type silicon layer 35) on both sides, and finally forming a silver film or an aluminum film as a p-type electrode 31 on the back side.

[0074] The solar cell element SB4 has a p-type GaAs layer 37 functioning as a contact layer, a p-type GaAs layer 39 formed on the p-type GaAs layer functioning as a light absorbing layer, and an n-type GaAs layer 41 formed on the p-type GaAs layer 39. In this way, the solar cell element SB4 is configured.

[0075] In addition, the solar cell element SB5 has: a p-type InGaP layer 43 that functions as a light absorption layer, an n-type InGaP layer 45 formed on the p-type InGaP layer 43, and an n-type electrode (for example, an alloy electrode of AuGeNi / Au or Ti / Au) 47 formed on the n-type InGaP layer 45. In this way, the solar cell element SB5 is formed. Here, the solar cell element SB4 and the solar cell element SB5 are formed on a semiconductor chip, and the solar cell element SB4 and the solar cell element SB5 are joined by a tunnel layer 49 formed on the semiconductor chip, and are also electrically connected in series. For example, the tunnel layer is composed of a degenerate semiconductor layer sandwiched between the n-type GaAs layer 41 of the solar cell element SB4 and the p-type InGaP layer 43 of the solar cell element SB5. As a result, the n-type GaAs layer 41 of the solar cell element SB4 and the p-type InGaP layer 43 of the solar cell element SB5 are electrically connected.

[0076] It should be noted that the solar cell element SB4 and the solar cell element SB5 are manufactured using a common process, that is, after sequential epitaxial growth on a cleaned GaAs substrate, the stacked structure of the solar cell element SB4 and the solar cell element SB5 is separated from the GaAs substrate by the ELO method.

[0077] On the other hand, the crystal structure of solar cell element SB3 is fundamentally different from that of solar cell element SB4 and solar cell element SB5, and therefore cannot be formed together by crystal growth. Therefore, solar cell element SB3 is formed on a semiconductor substrate different from the semiconductor substrate on which solar cell element SB4 and solar cell element SB5 are formed.

[0078] Then, by Figure 2The method shown in the embodiment forms an arrangement of conductive nanoparticles 23 on the solar cell element SB3, and then selectively erodes only the portion contacted by the conductive nanoparticles 23. Then, the semiconductor chip formed with the solar cell element SB3 and the semiconductor chip formed with the solar cell element SB4 and the solar cell element SB5 are overlapped and pressurized. Thus, the solar cell element SB3, the solar cell element SB4 and the solar cell element SB5 are mechanically joined and electrically connected through a plurality of conductive nanoparticles 23. Here, the solar cell element SB3, the solar cell element SB4 and the solar cell element SB5 have different band gaps, and as described in the embodiment 1, an electromotive force is generated in each solar cell element, and the multi-junction solar cell 3 generates a total electromotive force of each electromotive force as a whole. Through this embodiment, the same effect as the embodiment 1 can also be achieved.

[0079] (Implementation method 3)

[0080] Figure 5 The structure diagram of a semiconductor device (multi-junction solar cell) according to another embodiment is shown. The multi-junction solar cell 5 has a solar cell element SB1 of a bottom unit, a solar cell element SB4 of a middle unit, and a solar cell element SB5 of a top unit. The solar cell element SB1 is composed of a silicon unit, the solar cell element SB4 is composed of a GaAs unit, and the solar cell element SB5 is composed of an InGaP unit. That is, the solar cell element SB1 and Figure 1 The solar cell element SB1 of the multi-junction solar cell 1 has the same structure, and the solar cell element SB4 and the solar cell element SB5 are the same as Figure 4 The solar cell element SB4 and the solar cell element SB5 of the multi-junction solar cell 3 have the same structure, so the description is omitted. The production of these solar cell elements SB1, solar cell elements SB4 and solar cell elements SB5, the arrangement of the conductive nanoparticles 23 on the solar cell element SB1, the erosion of the contact parts of the conductive nanoparticles 23, the bonding of the solar cell element SB1 with the solar cell elements SB4 and the solar cell elements SB5, etc. are carried out by the same method as the above-mentioned embodiment. This is also common in the following embodiments. Through this embodiment, the same effect as embodiment 1 can also be achieved. Here, the solar cell element SB1 is called back barrier (BSF: Back Surface Field: back field) type silicon, which is a silicon unit that can achieve high efficiency by making the side of the p-type silicon substrate 13 close to the p-type electrode 11 a high-concentration p-type layer to reduce the loss of electrons near the electrode.

[0081] (Implementation 4)

[0082] Figure 6 A diagram showing the structure of a semiconductor device (multi-junction solar cell) according to another embodiment is shown. The multi-junction solar cell 7 has a solar cell element SB6 of a bottom unit, a solar cell element SB4 of a middle unit, and a solar cell element SB5 of a top unit, wherein the solar cell element SB6 is composed of a silicon unit, the solar cell element SB4 is composed of a GaAs unit, and the solar cell element SB5 is composed of an InGaP unit.

[0083] The solar cell element SB6 includes, for example, a p-type amorphous silicon layer 53 having a p-type electrode 51 formed of an aluminum film or a silver film, an i-type amorphous silicon layer 55 formed on the p-type amorphous silicon layer 53, an n-type silicon substrate 57 as a light absorbing layer formed on the i-type amorphous silicon layer 55, the i-type amorphous silicon layer 55 formed on the n-type silicon substrate 57, and an n-type amorphous silicon layer 61 formed on the i-type amorphous silicon layer 55. Figure 1 ) Similarly, an oxidized region 25 is generated entirely or partially on the surface of the n-type amorphous silicon layer 61. In this way, the solar cell element SB6 is formed.

[0084] The solar cell element SB6 is manufactured by the following method. That is, it is obtained by forming an i-type amorphous silicon layer 55 on both sides of an n-type silicon substrate 57 whose surface has been cleaned, then forming a conductive amorphous silicon layer (p-type amorphous silicon layer 53, n-type amorphous silicon layer 61) on both sides, and finally forming a silver film or an aluminum film as a p-type electrode 51 on the back side.

[0085] Solar cell element SB4 and solar cell element SB5 are Figure 4 and Figure 5 The solar cell element SB4 and the solar cell element SB5 of the multi-junction solar cells 3 and 5 have the same structure, so the description is omitted. Through this embodiment, the same effect as the embodiment 1 can also be achieved. The solar cell element SB6 is called a heterojunction type (HIT: Hetero junction with Intrinsic Thin-layer: heterojunction with intrinsic thin layer) silicon unit or a heterojunction junction type (HJT: Hetero Junction Technology: heterojunction technology) silicon unit, which is a high-efficiency silicon unit that reduces current loss by forming a p-type amorphous silicon layer 53 and an n-type amorphous silicon layer 61 as a unit contact layer through an i-type amorphous silicon layer 55.

[0086] It should be noted that the constituent materials of the solar cell elements that become the top unit and the middle unit are not limited to GaAs, InGaP, etc., and AlGaAs, InGaAsP, AlInGaP, InGaAs, chalcogenide-based (Cu(In, Ga)Se2(CIGS)), perovskite-based, organic-based, etc. materials can also be used. In addition, the structure of the silicon unit of the bottom unit is also diverse, but the top silicon layer that becomes the bonding surface is formed with an oxidized region, which is common, and obviously this technology can be applied.

[0087] Example

[0088] The following method was used to produce Figure 4 A multi-junction solar cell 3 is shown.

[0089] First, the solar cell element SB3 is produced by the following method.

[0090] The surface of the p-type silicon substrate 33 is treated with a dilute hydrofluoric acid-based etchant, and then a SiOx tunnel layer 32 of a thin film of about 1 nm is formed on both sides by chemical oxidation. Here, the oxide film is formed by immersing the p-type silicon substrate 33 in a concentrated nitric acid solution, but oxidation can also be performed using a CVD method or the like. Then, a 100nm p-type silicon layer (amorphous) 30 and an n-type silicon (amorphous) layer 35 are formed by chemical vapor deposition (CVD method), and then the amorphous layer is polycrystallized by annealing at 800°C. Finally, a sputtering method is used to form an aluminum film of about 500nm thickness to become the p-type electrode 31. It should be noted that the process of the solar cell element SB3 is carried out with a diameter of 4 inches and a thickness of 300μm, and finally cut into a 1cm square to make a bottom unit.

[0091] Next, the solar cell element SB4 and the solar cell element SB5 were fabricated by the following method. On the p-type GaAs substrate whose surface was cleaned with an ethanol solution, a p-type GaAs layer 37, a p-type GaAs layer 39, an n-type GaAs layer 41, a tunnel layer 49, a p-type InGaP layer 43, and an n-type InGaP layer 45 were sequentially formed via a peeling layer by using a molecular beam crystal growth method (Molecular Beam Epitaxy method: molecular beam epitaxy method) (using a molecular beam epitaxy device (Compact 21 solid source MBE) manufactured by Riber Corporation, and the growth temperature was 550° C.), and then, an n-type electrode 47 composed of AuGeNi / Au was formed by using an electron beam evaporation device (SVC-700LEB / 4G manufactured by Sanyu Electronics Co., Ltd., and the film formation rate was 2-4 angstroms / second). Here, the peeling layer is required for peeling from the substrate in the ELO process, and a 50nm AlAs layer is used. The process of solar cell elements SB4 and SB5 is carried out with a diameter of 2 inches and a thickness of about 350μm (GaAs substrate is about 340μm), and finally cut into 4mm squares and applied as top units. Then, the cut top unit is immersed in HF solution (solution concentration 20% by mass) for 12 hours and peeled off from the GaAs substrate to obtain a component composed of solar cells SB4 and SB5. It should be pointed out that the total thickness of the solar cell element SB4 and the solar cell element SB5 after peeling is about 4μm.

[0092] Next, the arrangement of the conductive nanoparticles 23 is formed on the solar cell element SB3 by the following method. The Pd nanoparticles as the conductive nanoparticles 23 are arranged on the solar cell element SB3 by thin-filming polystyrene-poly-2-vinylpyridine as a block copolymer and using it as a template. That is, a 0.5 mass % o-xylene solution of polystyrene-poly-2-vinylpyridine (polystyrene molecular weight: 133000 g / mol, poly-2-vinylpyridine molecular weight: 132000 g / mol) with a total molecular weight of 265000 g / mol is spin-coated on the solar cell element SB3 to form a thin film. Next, the solar cell element SB3 is immersed in a 1mM Na2PdCl4 aqueous solution for two minutes. After washing with water, the solar cell element SB3 is subjected to argon plasma treatment (using a plasma device (Femto) manufactured by Diener Company, treated at 50W for 2 minutes) to arrange the Pd nanoparticles with an average size (diameter) of 50nm that are not covered by organic molecules in an orderly manner. The average spacing between palladium nanoparticles in this configuration is 100 nm.

[0093] Next, the solar cell element SB3 was subjected to MACE treatment to selectively erode only the portion contacted by the Pd nanoparticles, thereby causing the Pd nanoparticles to sink (refer to Figure 2 (C)). This treatment is performed by using H2O2 / HF solution (using 30 mass % H2O2 solution and 50 mass % HF solution, the solution ratio is set to H2O2: HF: H2O = 1: 1: 10) as an etching solution, and immersing the solar cell element SB3 configured with Pd nanoparticles in the etching solution (25°C) for 1 minute. Then, the entire solar cell element SB3 is washed with water to remove the etching solution.

[0094] Next, the solar cell elements SB4 and SB5 were stacked on the solar cell element SB3 on which the Pd nanoparticles were arranged, and a weight (5 N / cm 2 ), thereby bonding the solar cell element SB3, the solar cell element SB4 and the solar cell element SB5. This solar cell is referred to as sample A.

[0095] In addition, for comparison, we also made Figure 7 The multi-junction solar cell 8 shown and Figure 8 The multi-junction solar cell 9 shown. The multi-junction solar cell 8 ( Figure 7 ) is obtained as follows: After forming the arrangement of the conductive nanoparticles 23 (Pd nanoparticles) (refer to Figure 2 (B)), without MACE treatment ( Figure 2 (C)), and after the solar cell element SB4 and the solar cell element SB5 are stacked on the solar cell element SB3 provided with the conductive nanoparticles 23, a pressurization treatment (5 N / cm 2 ), thereby joining the solar cell element SB3, the solar cell element SB4 and the solar cell element SB5. Other conditions are the same as those of the method for making the multi-junction solar cell 3. This solar cell is referred to as sample B.

[0096] In addition, multi-junction solar cells 9 ( Figure 8 ) is produced by the following method. As described above, the existence of an oxidized region on the surface of the silicon cell increases the junction resistance between cells and affects the characteristics of the solar cell, but the multi-junction solar cell 9 is processed to remove the oxidized region.

[0097] First, solar cell element SB3, solar cell element SB4, and solar cell element SB5 were produced by the same method as that of multi-junction solar cell 3. Next, before forming the arrangement of conductive nanoparticles 23 (Pd nanoparticles), a buffered HF solution (a mixture of hydrofluoric acid and ammonium fluoride, also called BHF solution) was used to remove part or all of the oxidized region 25 formed on the surface of solar cell element SB3 (solar cell element SB7). Specifically, a BHF solution (manufactured by Daikin Industries, Ltd., BHF63) was used, and solar cell element SB3 was immersed in the BHF solution (25° C.) for 1 minute (BHF treatment).

[0098] Then, the conductive nanoparticles 23 are arranged in the same manner as in the case of the multi-junction solar cell 3 (see Figure 2 (B)). Then, without MACE treatment, the solar cell elements SB4 and SB5 were stacked on the solar cell element SB7 provided with the conductive nanoparticles 23, and then a pressurization treatment (5 N / cm 2 ), thereby bonding the solar cell element SB7, the solar cell element SB4, and the solar cell element SB5. This solar cell is referred to as sample C.

[0099] Fig. 9 The current-voltage characteristics (IV curve) of the solar cell of sample AC produced by the above method are shown in . This measurement was performed using an IV simulator (manufactured by Bunkoukeiki Co., Ltd., model 38A042Y) and irradiating simulated sunlight with AM (atmospheric mass) of 1.5G.

[0100] In addition, from Fig. 9 The short-circuit current density (Js) of the sample AC is extracted from the current-voltage characteristics c The results of the tests are shown in Table 1.

[0101] [Table 1]

[0102] Measurement results of solar cell characteristics

[0103]

[0104] Regarding the solar cells of sample A and sample C, the results showed good cell performance. In particular, the solar cell of sample A showed excellent cell characteristics in all items. Regarding the solar cell of sample C, although it was treated with BHF, it is also considered that a part of the oxidized area remains, and the characteristics may be deteriorated. On the other hand, regarding the solar cell of sample A, the Pd nanoparticles penetrate the oxidized area through the MACE treatment and enter the n-type silicon layer 35, so that the conductivity is good. In this way, the solar cell of sample A, in particular, has a sufficiently low junction resistance due to the lack of the influence of the oxidized area, and obtains a high power generation efficiency of more than 30%. Regarding the short-circuit current, it is also increased by 1mA / cm compared with other samples. 2 . This is because, by reducing the exposure height of the Pd nanoparticles through the MACE method, the interval (H) between the solar cell element SB3 and the solar cell element SB4 becomes less than 10nm, so the reflection loss at the junction interface is reduced. Therefore, it is believed that the photocurrent of the solar cell element SB3 of sample A increases, and the current matching level of the multi-junction battery increases. On the other hand, for the solar cell of sample B, the resistance of the junction part becomes higher due to the influence of the oxidation region 25, forming an S-shaped curve shape.

[0105] Fig.10 : shows an atomic force microscope (AFM) photograph of the Si surface of sample A after MACE treatment. Fig.10 (A) is the view from the top surface. Fig.10 (B) is a three-dimensional view from the oblique direction. Fig.11 (A) shows the AFM photo (left) and optical microscope photo (right) of the Si surface after the Pd nanoparticles of sample B are arranged. Fig.11 (B) shows an AFM photograph (left) and an optical microscope photograph (right) of the Si surface after the Pd nanoparticles are arranged in sample C. Atomic force microscopy observation was performed using a microscope (SPM9600, manufactured by Shimadzu Corporation).

[0106] Regarding the solar cell of sample A ( Fig.10 ), the arrangement of the conductive nanoparticles 23 (Pd nanoparticles) is clear, and some Pd nanoparticles are found to be precipitated (X part) due to the influence of MACE treatment, but there is no large abnormal precipitation. On the other hand, for the solar cell of sample C ( Fig.11(B)), due to the BHF treatment, bumps and surface defects are generated in the silicon layer, thereby hindering the uniform arrangement of the conductive nanoparticles 23 (Pd nanoparticles), and in particular inducing surface defects, resulting in abnormal precipitation of Pd nanoparticles with a height of more than 100nm (Y part). Here, in the MACE method (sample A), since the treatment is performed after the arrangement of the conductive nanoparticles 23, the part without the conductive nanoparticles 23 is ideally not corroded, and only the part directly below the conductive nanoparticles 23 is uniformly corroded and sinks. Therefore, the smoothness of the conductive nanoparticles 23 is maintained as a whole, and the degree of bumps and bumps becomes smaller than that in the case of the BHF treatment (sample C). It should be noted that with respect to the solar cell of sample B ( Fig.11 In (A), since no surface treatment such as BHF treatment or MACE treatment is performed, the arrangement of the conductive nanoparticles 23 (Pd nanoparticles) is uniform.

[0107] Next, for the solar cells of sample AC, appearance observation and observation using nitrogen blowing were performed from the perspective of comparing the bonding strength and stability. First, the appearance observation was performed using a stereo microscope. In addition, the observation using nitrogen blowing was performed using the following method. That is, a tubular glass tube (diameter 1 mm) with a thin tip was prepared, and nitrogen gas (pressure 5 Kg / cm 2 ). The evaluation results of the solar cells of samples AC are shown in Table 2. It should be noted that in Table 2, the performance of the solar cell is judged based on the results of Table 1.

[0108] [Table 2]

[0109] Solar cell evaluation

[0110]

[0111] Fig.12 (A)-(C) show the appearance photos (upper surface) of the solar cells of each sample A to C. Fig.12 (A)) and sample B ( Fig.12 In the solar cell of sample (B), no particular abnormality was found, but in the solar cell of sample C, Fig.12 As shown in (C), the unjoined areas (gaps) appear to float, and air intrusion is found. In addition, in the observation using nitrogen blowing, Fig.13 As shown, in sample A ( Fig.13 (A)) and sample B ( Fig.13 In the solar cell of sample (B), no particular abnormality was found, but in sample C ( Fig.13In the solar cell of (C), damage such as scattering and peeling occurred. Since Pd nanoparticles are used to bond the units, if the height of the Pd nanoparticles is uniform, the bonding strength will be better. However, in sample C, as shown in FIG. Fig.11 As shown in (B), abnormal precipitation of Pd nanoparticles occurred, and it is considered that the bonding strength decreased.

[0112] Fig.14 TEM (transmission electron microscope) image (A) of sample A and analysis results based on energy dispersive X-ray spectroscopy (B) are shown in FIG. Fig.15 TEM image (A) and analysis result (B) based on energy dispersive X-ray spectroscopy of sample B are shown in FIG. TEM image is measured with transmission electron microscope (H-9500 manufactured by Hitachi High-Technologies Corporation, accelerating voltage 200 kV). In addition, energy dispersive X-ray spectroscopy is measured with electron microscope (JEOL Ltd., JEM-ARM200F, accelerating voltage 200 kV).

[0113] like Fig.14 As shown in the figure, when the Pd nanoparticles are observed by TEM magnification, it is a domain structure composed of Pd nanoparticles of about several nm. In the solar cell of sample A, the Pd nanoparticles constituting the domain are observed to enter the n-type silicon layer (polycrystalline) below the bonding gap (8nm) (more than 10nm). It should be pointed out that the surrounding oxidized area without Pd nanoparticles is directly etched by the HF:H2O2 solution during the MACE process, but it is believed that it remains as a thin film at the microscopic level.

[0114] In addition, in the data of energy dispersive X-ray spectroscopy of sample A, a Pd signal was also observed in the n-type silicon layer (polycrystalline), confirming the invasion of Pd nanoparticles. On the other hand, for the solar cell of sample B, an oxidized region with a thickness of about 10 nm was observed on the surface of the silicon unit, and the Pd nanoparticles did not invade the n-type silicon layer (polycrystalline) but only existed in the joint gap. The Pd signal of energy dispersive X-ray spectroscopy is also different from that of sample A and is only observed in the joint gap. It should be pointed out that, although not shown in the figure, in sample C, the oxidized region was removed by BHF treatment, and Pd nanoparticles were only observed in the joint gap. In sample A, since the Pd nanoparticles enter the interior of the n-type silicon layer (polycrystalline), the junction resistance is reduced without being affected by the oxidized region, and a joint structure with excellent joint strength is formed by the so-called anchoring effect. Regarding sample B, due to the surface oxidation region of the silicon semiconductor, the junction resistance increases and the battery performance deteriorates. Regarding sample C, the oxidized area on the silicon surface was removed by BHF treatment, but the abnormal precipitation of Pd caused by the aforementioned surface defects resulted in deterioration of the bonding strength. Therefore, according to this embodiment, a high-efficiency multi-junction solar cell having a bonding structure with excellent bonding strength and excellent cell performance can be easily provided, which can improve the reliability of the solar cell.

[0115] It should be noted that, according to the above embodiment, the oxidized region is not removed and the conductive nanoparticles 23 are sunk into the silicon layer, but a process of removing the oxidized region may be added and then a process of sinking the conductive nanoparticles 23 may be performed. That is, the presence or absence of the oxidized region is not particularly limited, and if the conductive nanoparticles 23 enter the silicon layer, the same effects as those of the above embodiment are achieved.

[0116] In the above embodiment, a multi-junction solar cell is exemplified as a semiconductor device, but the present invention can also be applied to an optical integrated element or a silicon photonic element in which a Si semiconductor element and a plurality of semiconductor elements are connected in series.

[0117] Description of Reference Numerals

[0118] 1, 3, 5, 7, 8, 9 multi-junction solar cells

[0119] 11p type electrode

[0120] 13 p-type silicon substrate

[0121] 15 n-type silicon layer

[0122] 17p-type GaAs layer

[0123] 19n-type GaAs layer

[0124] 21 n-type electrode

[0125] 23 Conductive Nanoparticles

[0126] 25 Oxidation Area

[0127] 27 Etching area

[0128] 30 p-type silicon layer

[0129] 31 p-type electrode

[0130] 32SiOx tunnel layer

[0131] 33 p-type silicon substrate

[0132] 35 n-type silicon layer

[0133] 37p-type GaAs layer

[0134] 39p-type GaAs layer

[0135] 41n-type GaAs layer

[0136] 43p-type InGaP layer

[0137] 45n-type InGaP layer

[0138] 47 n-type electrode

[0139] 49 Tunnel Layer

[0140] 51 p-type electrode

[0141] 53 p-type amorphous silicon layer

[0142] 55 i-type amorphous silicon layer

[0143] 57 n-type silicon substrate

[0144] 61 n-type amorphous silicon layer.

Claims

1. A semiconductor device comprising: A first semiconductor element includes a silicon layer and has a first bonding surface; a second semiconductor element having a second bonding surface opposite to the first bonding surface; and A plurality of conductive nanoparticles are located between the first bonding surface and the second bonding surface, electrically connecting the first semiconductor element and the second semiconductor element. The plurality of conductive nanoparticles enter into the silicon layer.

2. The semiconductor device according to claim 1, wherein The plurality of conductive nanoparticles each contain any one of palladium, gold, silver, platinum, nickel, aluminum, indium, indium oxide, zinc, zinc oxide, and copper.

3. The semiconductor device according to claim 1, wherein The exposed height of the plurality of conductive nanoparticles is less than 20 nm, and the height of the plurality of conductive nanoparticles penetrating into the silicon layer is greater than 5 nm.

4. A solar cell comprising the semiconductor device according to any one of claims 1 to 3, wherein the silicon layer of the first semiconductor element comprises a semiconductor material of crystalline silicon or amorphous silicon, The second semiconductor element includes one or more semiconductor materials selected from GaAs, AlGaAs, InGaP, AlGaInP, InGaAsP, InGaAs, chalcogenide-based, perovskite-based, and organic-based.

5. A method for manufacturing a semiconductor device, comprising: (a) step of preparing a first semiconductor element including a silicon layer and having a first bonding surface; (b) step of preparing a second semiconductor element having a second bonding surface; (c) step of disposing a plurality of conductive nanoparticles on the first bonding surface; (d) step of causing a plurality of conductive nanoparticles to enter the silicon layer after the step (c); and (e) After the step (d), the second bonding surface is placed opposite to the first bonding surface via the plurality of conductive nanoparticles and pressed.

6. The method for manufacturing a semiconductor device according to claim 5, wherein: As the plurality of conductive nanoparticles, particles of any one of palladium, gold, silver, platinum, nickel, aluminum, indium, indium oxide, zinc, zinc oxide, and copper are used.

7. The method for manufacturing a semiconductor device according to claim 5, wherein: The exposed height of the plurality of conductive nanoparticles is set to be 20 nm or less, and the height of the plurality of conductive nanoparticles penetrating into the silicon layer is set to be 5 nm or more.

8. A method for manufacturing a solar cell, comprising the method for manufacturing a semiconductor device according to any one of claims 5 to 7, wherein in the method for manufacturing a solar cell, A semiconductor material of crystalline silicon or amorphous silicon is used as the silicon layer of the first semiconductor element, and one or more semiconductor materials of GaAs, AlGaAs, InGaP, AlGaInP, InGaAsP, InGaAs, chalcogenide system, perovskite system, and organic system are used as the second semiconductor element.

9. The method for manufacturing a semiconductor device according to any one of claims 5 to 7, wherein: In the step (d), the conductive nanoparticles are introduced into the silicon layer by metal-assisted chemical etching.

10. The method for manufacturing a solar cell according to claim 8, wherein: In the step (d), the conductive nanoparticles are introduced into the silicon layer by metal-assisted chemical etching.

Citation Information

Patent Citations

  • Information setting device of camera

    JP1983075124A